The changing trend and prediction of the burden of anxiety disorder in Chinese population from 2022 to 2035 - Fan, Ruiheng; Pan, Ciming; Fang, Hui; Zhang, Jida (Frontiers in Public Health, 2025)
ObjectiveTo analyze the disease burden of anxiety disorders globally, in middle SDI countries, and in China using GBD public database.MethodsData on anxiety disorders were extracted from the GBD database, and GBDR_V2.36 was used for data visualization and plotting.ResultsFrom 1990 to 2021, global anxiety disorder cases and prevalence rose steadily. In 2021, the 30–34 age group had the highest global cases (male:female≈3:7), while DALY rates peaked in 25–29-year-olds. Medium-SDI countries followed similar trends, with peak DALYs in the 20–24 age group. China saw declining prevalence/incidence but rising DALYs, with highest cases in 50–54-year-olds (male:female≈3:5) and DALY rates in 75–84-year-olds. Globally, medium-SDI countries, and China, incidence peaked in 10–14-year-olds. Projections suggest China’s anxiety disorder burden will surge through 2035.ConclusionGlobally and in middle SDI countries, prevalence, incidence, and DALY rates increased, with the 30–34 age group showing the highest case burden (women outnumbering men) and peak DALY rates in younger adults (25–29 globally, 20–24 in middle SDI). In contrast, China saw a decline in prevalence and incidence, with the burden peaking later (50–54 for cases, 75–84 for DALYs). Projections indicate rising anxiety disorder burden in China by 2035, necessitating region- and age-specific interventions.